Dependability in sensor, cloud, and big data systems and applications : 5th International Conference, DependSys 2019, Guangzhou, China, November 12-15, 2019, Proceedings /: 5th International Conference, DependSys 2019, Guangzhou, China, November 12-15, 2019, Proceedings. (2019) - Unknown
No abstract available